PENGARUH PENGALAMAN KERJA, PROMOSI JABATAN DAN MUTASI TERHADAP PRESTASI KERJA KARYAWAN - Dahlia Wati; Merta Kusuma; Tezar Arianto ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2020)
Every company not only expects capable, capable and skilled employees but most importantly they want to work hard and want to achieve maximum work results. In an effort to improve work performance, work experience, promotions and mutations are needed. the purpose of this study was to determine the effect of work experience, promotion and mutation on the work performance of PT. Agro Muko-Mukomuko Estate. This research is a causal associative research using a quantitative approach. This study analyzes the effect of work experience, promotion and mutation on the work performance of employees of PT. Agro Muko-Mukomuko Estate. the population in this study were 70 employees of PT. Agro Muko-Mukomuko Estate. The sampling technique in this research is 70 saturated sampling techniques. In this study the data collection method used was Observation, Questionnaire Method (Questionnaire). Data analysis methods used are descriptive analysis and multiple linear regression analysis. Based on the results of data analysis, the results show that: 1) Partially, Work Experience, Job Promotion and Mutation variables influence the Job Performance of PT. Agro Muko-Mukomuko Estate. as evidenced by the magnitude of t-counts (2,286> 1.9965) and tsig< = 0.025 <0.050), (2,593> 1.9965) and (2,390> 1.9965) and tsig< = 0.020 <0.050),, Simultaneously the variables Work Experience, Job Promotion and Mutations affect the Job Performance of PT. agro Muko-Mukomuko Estate,as evidenced by the magnitude of 20,776 with a value of 1.8626, namely (20,776> 1.8626) and tsig< = 0,000 <0.050), This shows that the variable Work Experience (), Job Promotion (X2) and Mutation (X3) significantly influence Employee Performance (Y) in PT Agro Muko-Muko Estate Employees. Keywords : Work Experience, Position Promotion, Mutation, and Job Performance.